robo-CAMAL: A BDI Motivational Robot - Davis Darryl (Paladyn: Journal of Behavioral Robotics, 2010)
Motivation is a central concept in the development of autonomous agents and robots. This paper describes an architecture that uses a psychological BDI model of reasoning, combined with a distributed multi-level model of motivation. The robot controlling architecture makes use of a generic set of deliberative components plus an environment task-centred set of reactive components that reflect the architecture's embodiment. The architecture has been used in a number of simulated environments and here is used to control a mobile robot. A theoretical framework for motivation and affect is given, and related to the nature of autonomy and embodiment. A BDI model, based on a psychological model of reasoning in a 5 year old child, is described in terms of the nature of motivation and affect within the architecture. Finally, criteria for judging the nature of an agent's motivation are introduced, and used to validate the motivational constructs implemented within the architecture. Experimental results lead to a comparative discussion.